Self-Tuning Regulator (STR) on Solar Energy-Based Herbs Drying System - Hong, Wong Chiew; A.jalil @ Zainuddin, Mohd Hafiz; Hamdan, Rohaiza; Mei Lik, Lock (Evolution in Electrical and Electronic Engineering, 2020)
This study emphasized on controller design for improving temperature regulation for solar based-energy herbs drying system. Therefore, the Self-Tuning Regulator (STR) controller is adapted on temperature regulation of solar based-energy herbs drying system. The transient analysis of the response found that Self-Tuning Regulator (STR) capable to prevent the response from the overshoot and provide 64.9% faster settling time as compared with PID controller.